2006
DOI: 10.1029/2006jd007306
|View full text |Cite
|
Sign up to set email alerts
|

Large upper tropospheric ozone enhancements above midlatitude North America during summer: In situ evidence from the IONS and MOZAIC ozone measurement network

Abstract: The most extensive set of free tropospheric ozone measurements ever compiled across midlatitude North America was measured with daily ozonesondes, commercial aircraft and a lidar at 14 sites during July-August 2004. The model estimated stratospheric ozone was subtracted from all profiles, leaving a tropospheric residual ozone. On average the upper troposphere above midlatitude eastern North America contained 15 ppbv more tropospheric residual ozone than the more polluted layer between the surface and 2 km abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
124
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(142 citation statements)
references
References 55 publications
18
124
0
Order By: Relevance
“…Both models simulate that NO x concentrations decrease by a factor of >5 from the Southeast to the Northeast and Eastern Canada, much larger than a factor of 2 or less in the measurements. Similar large biases in the simulated south-to-north decrease of lightning NO x over Eastern North America can also be found in previous studies (e.g., Li et al, 2005;Hudman et al, 2007;Cooper et al, 2006 and. Figure 1a shows that convective mass fluxes in the upper troposphere in both WRF and MM5 are generally low over the Northeast.…”
Section: Effect Of Lightning No X During Intex-asupporting
confidence: 70%
See 2 more Smart Citations
“…Both models simulate that NO x concentrations decrease by a factor of >5 from the Southeast to the Northeast and Eastern Canada, much larger than a factor of 2 or less in the measurements. Similar large biases in the simulated south-to-north decrease of lightning NO x over Eastern North America can also be found in previous studies (e.g., Li et al, 2005;Hudman et al, 2007;Cooper et al, 2006 and. Figure 1a shows that convective mass fluxes in the upper troposphere in both WRF and MM5 are generally low over the Northeast.…”
Section: Effect Of Lightning No X During Intex-asupporting
confidence: 70%
“…Hudman et al (2007Hudman et al ( , 2009 found lightning can increase upper troposphere O 3 concentrations by 10-17 ppbv and Cooper et al (2006) found an increase of 11-13 ppbv on average and suggested a maximum of 24 ppbv based on the box model analysis during INTEX-A over the Eastern US. We find, here, that O 3 concentrations are increased by up to ∼20 ppbv (Fig.…”
Section: Effect Of Lightning No X During Intex-amentioning
confidence: 99%
See 1 more Smart Citation
“…However, the overall importance of stratospheric ozone intrusions to the tropospheric ozone budget depends on their distribution with geography and season, and on the fate of the exchanged air parcels, particularly their vertical penetration and residence time Cooper et al, 2004;Thompson et al 2007;Tarasick and Slater, 2008). For these reasons, at least in part, observational estimates of the stratospheric contribution vary widely (e.g., Bachmeier et al, 1994;Browell et al, 1994Browell et al, , 2003Mauzerall et al, 1996;Dibb et al, , 1997Dibb et al, , 2003Allen et al, 2003;Bazhanov and Rodhe, 1997;Elbern et al, 1997;Li et al, 2002;Cooper et al, 2006;Thompson et al 2007).…”
Section: For the Baqs-metmentioning
confidence: 99%
“…Budget analyses performed by Zhang et al [2003] showed that lightning contributes more than 50% of the upper tropospheric NO x over the United States from April to November, impacting the upper tropospheric O 3 budget by as much as 30%. Combined measurement and modeling studies performed by Cooper et al [2006Cooper et al [ , 2007 [Jacob, 1999;Martin et al, 2000], and (c) isentropic cross-tropopause transport of O 3 from the stratosphere [Allen et al, 2003;Jing et al, 2005].…”
mentioning
confidence: 99%